On Problem of Renewable Energy Source Usage in Energy Efficient Construction - V. M. Pilipenko; V. D. Akeliev; Ngo Tuan Kiet; Thuy Nga Nguyen (Известия высших учебных заведений и энергетических объединенний СНГ: Энергетика)
The paper presents dependences required for calculation of heat and energy  for building operation within the period of its functioning and mean specific power of heat loss.